Competitiveness management as a condition for ensuring successful entrepreneurial activity ("Journal "U". Economy. Management. Finance.", 2022)
The article deals with the issues of enterprise competitiveness management. The authors emphasize that a significant competitive advantage in the face of sanctions and the deepening crisis is cost reduction without loss of product quality. This can be achieved with the help of lean manufacturing technology, the ideas of which gained particular popularity at the beginning of the 21st century all over the world. However, lean production technology is not only a management concept, but also a business philosophy that can have a positive effect only if each employee is aware of his tasks and is involved in the process of improving the business processes of the enterprise.
Keywords: competitiveness; entrepreneurship; competition; competitive advantage; lean manufacturing; kanban; kaizen; product quality; development strategy; cost reduction